Molecular and bio-analytical characterisation as a means to understand genetic diversity within Kenyan Aspergillus flavus strains - Mitema, Alfred Ochieng (Department of Molecular and Cell Biology, 2018)
Toxigenic Aspergillus species produce mycotoxins that are carcinogenic, hepatotoxic and teratogenic immunosuppressing agents in both human and animals. Kenya frequently experiences outbreaks of aflatoxicosis with the worst occurring in 2004, which resulted in 125 deaths. This study sought to find possible reasons for frequent aflatoxicosis outbreaks in Kenya by isolating Aspergillus flavus strains from maize kernels sampled from different climatic regions of Kenya. Using diagonal transect random sampling, maize kernels were collected from Makueni, Homa Bay, Nandi, and Kisumu regions. The genetic diversity and variation among the isolates was examined by characterising the strains according to morphology, phenotype, vegetative compatible groups and molecular systematics. Selected atoxigenic and aflatoxigenic A. flavus isolates were also further analysed for aflatoxin production potential using quantitative real-time PCR and various bioanalytical techniques. The influence of the maize lines grown in Kisumu, Homa Bay, Nandi and Makueni region on A. flavus infection and aflatoxin production was also examined and served as the basis for an in vitro biocontrol assay. Out of 37 isolates identified, nitrate non-utilizing auxotroph’s complementation test revealed 20 vegetative compatibility groups. These groups were further designated using the prefix ʻʻKVCGʼʼ, where ʻʻKʼʼ represented Kenya and consequently assigned numbers 1 to 20 based on our findings. KVCG14 and KVCG15 had highest distribution frequency (n = 13; 10.8 %). The distribution of the L, S and S/L- morphotypes across the regions were 57 % (n = 21); 7 % (n = 3) and 36 % (n = 13) respectively. The phylogenetic analysis exhibited high diversity of A. flavus isolates from Makueni. ITS1 and ITS2 markers did not reveal significant information within intraspecies speciation of A. flavus. Furthermore, a unique isolate (KSM015) was identified that had characteristics of S-morphotype, but produced both aflatoxins B and G. Coconut agar medium (CAM) assay, TLC, HPLC and LCMS/MS analyses confirmed the presence or absence of aflatoxins in selected toxigenic and atoxigenic isolates. qPCR analysis revealed aflP, aflS, aflR and aflO transcripts as the most upregulated genes across the tested isolates whereas false detection of aflD gene transcript was observed in both induced and uninduced A. flavus isolates. Diversity Index (H) analyses ranged from 0.11 (Nandi samples) to 0.32 (Kisumu samples). Heterokaryon compatibility ranged from 33 % (for the Makueni samples, n = 3) to 67 % (Nandi samples, n = 6). The KDV1 maize line was more sensitive to A. flavus infection in comparison to GAF4. We also tested the biocontrol of atoxigenic isolates to inhibit toxin production by aflatoxigenic strains on infected maize kernels. It was shown that the atoxigenic strain (KSMO12) could inhibit the aflatoxigenic strain (KSM014) depending on the atoxigenic concentration during infection. To our knowledge, this is the first reported study for A. flavus genetic diversity, variation and distribution in Nandi, Homa Bay and Kisumu regions in comparison to and could assist researchers in the selection of biocontrol strategies to mitigate aflatoxin contamination, especially in Makueni and neighbouring regions.